STUDI PENYEDIAAN AIR BERSIH DI DESA SULAMU MENGGUNAKAN TEKNOLOGI PHOTOVOLTAIC- SEA WATER REVERSE OSMOSIS - Arbye S; Achmad Aziizudin; Agung Purnomo; Cahyo Wibi Yogiswara; Dimas Ardiansyah Halim; Setya Drana Harry Putra (Scientific Journal of Mechanical Engineering Kinematika, 2024)
The scarcity of clean water is predicted to become a serious threat for Indonesia in the future, particularly in regions with low rainfall, and coastal regions with limited freshwater resources. This study examined clean water provision using seawater desalination technology in Sulamu Village, Kupang, East Nusa Tenggara, projected until 2032. The technology used was seawater desalination powered by Photovoltaic (PV) systems, which drive the Sea Water Reverse Osmosis (SWRO) process. This technology was proposed as a sustainable solution to meet the clean water needs of the region. The research included an analysis of water demand, adjusted for projected population growth, and an estimation of energy consumption from the PV-SWRO system. A geometric method was applied to project the population up to 2032, estimating approximately 8.210 residents. Based on this projection, the clean water demand was expected to reach 215.769 m³ per year, with energy consumption estimated between 496 and 1.554 MWh per year. Given the abundant solar energy potential in Sulamu Village, this technology is anticipated to provide a stable and environmentally friendly supply of clean water. The estimated data on water and energy needs is intended to serve as a reference for stakeholders in developing strategies that support the sustainability of renewable energy-based desalination programs in the future.